2020
DOI: 10.3389/fbioe.2020.00689
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Human Stromal Vascular Fraction Cells on Nanofibrillar Scaffolds for Treatment of Peripheral Arterial Disease

Abstract: Cell therapy for treatment of peripheral arterial disease (PAD) is a promising approach but is limited by poor cell survival when cells are delivered using saline. The objective of this study was to examine the feasibility of aligned nanofibrillar scaffolds as a vehicle for the delivery of human stromal vascular fraction (SVF), and then to assess the efficacy of the cell-seeded scaffolds in a murine model of PAD. Flow cytometric analysis was performed to characterize the phenotype of SVF cells from freshly iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The recovery mechanisms underlying this therapeutic effect may include both angiogenesis and arteriogenesis, which could be mediated by patterned scaffold-induced activation of integrin-α1 and increased VEGF secretion. 54,63,64 These studies demonstrate an important role of nanopatterning cues in directing cell behavior, which can be applied toward improving the survival and angiogenic function of implanted cells in the setting of limb ischemia.…”
Section: Bioengineering Approaches To Enhance Posttransplant Cell Sur...mentioning
confidence: 94%
See 2 more Smart Citations
“…The recovery mechanisms underlying this therapeutic effect may include both angiogenesis and arteriogenesis, which could be mediated by patterned scaffold-induced activation of integrin-α1 and increased VEGF secretion. 54,63,64 These studies demonstrate an important role of nanopatterning cues in directing cell behavior, which can be applied toward improving the survival and angiogenic function of implanted cells in the setting of limb ischemia.…”
Section: Bioengineering Approaches To Enhance Posttransplant Cell Sur...mentioning
confidence: 94%
“…In vitro studies showed that SVF cells cultured on the scaffold had a 6-fold higher level of VEGF secretion, compared with that of SVF cells cultured in suspension. 63 Importantly, when SVF-seeded scaffolds were transplanted into immunodeficient mice with induced hind limb ischemia, the cell-seeded scaffolds induced a significant higher mean perfusion ratio after 14 days, compared with cells delivered in saline. 63 These findings show that both ECs and SVF cells delivered on aligned nanofibrillar scaffolds into ischemic tissue stimulated blood perfusion recovery.…”
Section: Biophysical Patterning Cues In Biomaterialsmentioning
confidence: 98%
See 1 more Smart Citation
“…6 ). Seeding of stromal vascular fraction nanomaterials enhances blood perfusion recovery in a mouse model of peripheral arterial disease [101] . Similarly, engineered vessel grafts show a promising alternative to autografts in coronary artery bypass surgery.…”
Section: Main Textmentioning
confidence: 99%
“… 11 Several studies already reported that SVF supports tissue revascularization along with the secretion of the angiogenic factors including vascular endothelial growth factor (VEGF) and hepatic growth factor (HGF). 12 14 Recently, Muller et al 15 showed that SVF spheroids exhibit a high angiogenic potential and promote the formation of new blood vessels after in vivo transplantation.…”
Section: Introductionmentioning
confidence: 99%